2009
DOI: 10.1111/j.1743-6109.2009.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Ameliorates Diabetes-Induced Changes in Vaginal Structure of db/db Mouse Model

Abstract: Introduction Women with diabetes experience diminished genital arousal, reduced vaginal lubrication, vaginal atrophy, dyspareunia, and increased infections. Limited studies are available investigating the effects of diabetic complications on the vagina. Aims The goals of this study were to investigate type 2 diabetes-induced changes in vaginal structure, and to determine if estradiol treatment ameliorates these changes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 42 publications
4
24
0
Order By: Relevance
“…We further demonstrate that estradiol supplementation in diabetic animals restores most of these diabetes-induced changes in the vagina. Our previous study using the same animal model suggests that the restorative effect of estradiol supplementation occurs despite the persistence of hyperglycemia [19]. Because the vagina is a target tissue for sex steroids, it is likely that diabetes-induced changes in receptor expression impede vaginal tissue physiological function.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We further demonstrate that estradiol supplementation in diabetic animals restores most of these diabetes-induced changes in the vagina. Our previous study using the same animal model suggests that the restorative effect of estradiol supplementation occurs despite the persistence of hyperglycemia [19]. Because the vagina is a target tissue for sex steroids, it is likely that diabetes-induced changes in receptor expression impede vaginal tissue physiological function.…”
Section: Discussionmentioning
confidence: 97%
“…Mice were housed 2-3 animals per cage with food and water available ad libitum. Blood glucose levels were determined at 12 and 16 weeks of age, using an Accu-check blood glucose meter (Roche Diagnostics, Basel, Switzerland) as previously described [15,19]. Animals were considered diabetic when blood glucose level exceeded 250 mg/dl (13.86 mmol/L).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…However a divisive study [29] showed that estrogen treatment in women decreased collagen content compared to placebo treatment. Estradiol administration in diabetic mouse significantly increased the volume of the muscle layer and the lamina propria, but induced less marked changes in elastic fibers [30].…”
Section: Discussionmentioning
confidence: 87%